Method for preparing composite ferric sodium pyrophosphate through sulfur circulation

Through the sulfur cycle preparation method, ferrous sulfate is used to replace ferrous nitrate to prepare composite sodium ferrous pyrophosphate, which solves the problems of impurities affecting capacity and high cost and environmental pollution in NFPP, and achieves a high-capacity sodium ion battery positive electrode material with low cost, high safety and environmental protection.

CN119503748AActive Publication Date: 2025-02-25SHENZHEN JANAENERGY TECH CO LTD +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411689321.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-25
Estimated Expiration
2044-11-25

AI Technical Summary

Technical Problem

The existing sodium ion battery cathode material composite sodium ferric phosphate (NFPP) produces impurities of sodium ferric phosphate during the preparation process, resulting in a low actual capacity, and the use of iron nitrate as an iron source has high costs, environmental pollution and safety hazards.

Method used

The sulfur cycle preparation method is adopted, by wet mixing ferrous sulfate, sodium source, phosphorus source and dispersant, spray-drying, and calcining at high temperature under a protective atmosphere to obtain composite sodium ferrous phosphate, and the SO2 in the exhaust gas is converted into SO3 through a multi-layer vanadium pentoxide catalyst to form sulfuric acid, which is used to synthesize ferrous sulfate again to realize material circulation.

Benefits of technology

The preparation cost is reduced, the reversible specific capacity of the material is increased, and due to the use of ferrous sulfate, the material has higher safety and better environmental protection, and is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a method for preparing composite ferric sodium pyrophosphate by sulfur cycle, which comprises the following steps: S1, preparation of composite ferric sodium pyrophosphate: mixing ferrous sulfate, a sodium source, a phosphorus source and a dispersing agent by a wet process, spray-drying to obtain a precursor, and calcining at high temperature under a protective atmosphere to obtain the composite ferric sodium pyrophosphate; s2, tail gas recovery and conversion: sulfur-containing tail gas generated in the high-temperature calcination process of the precursor and air pass through a multi-layer vanadium pentoxide catalyst, and temperature control reaction is performed to convert SO2 into SO3, so that SO3 tail gas is obtained; s3, SO3 tail gas collection and conversion: SO3 tail gas is transferred into a sulfuric acid collector through temperature control of a heat exchanger, so that SO3 and H2O are cooled and converted into a sulfuric acid solution; and S4, preparation of ferrous sulfate: adding an iron source into a sulfuric acid solution, carrying out heating reaction, carrying out solid-liquid separation, cooling, and adding a reducing agent for reaction to obtain the ferrous sulfate used in the step S1. The preparation method has the characteristics of low cost, high reversible specific capacity and environment friendliness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sodium ion batteries, and in particular to a method for preparing composite sodium iron pyrophosphate by sulfur circulation. Background Art

[0002] Lithium-ion batteries are a new type of secondary battery that has attracted much attention. Due to their excellent theoretical capacity, reliable cycle performance, environmental protection, high safety and other advantages, lithium-ion batteries have become core components of electric vehicles, electronic products and other important commercial fields. However, with the growing demand for lithium-ion batteries, the cost of lithium resources has also increased year by year. In addition, the geographical distribution of lithium resources is uneven, so scientists have invested in the research of sodium, which has similar properties to lithium and is abundant. Sodium-ion batteries with excellent performance require positive electrode materials with excellent electrochemical properties.

[0003] Among the positive electrode materials of sodium ion batteries, polyanion sodium ion batteries have attracted market attention due to their good structural stability and thermal stability, low cost, and excellent cycle stability. At present, the most studied polyanion material is composite sodium iron phosphate (Na4Fe3(PO4)2P2O7, abbreviated as NFPP), which has an open three-dimensional framework structure and contains PO4 3− and P2O7 4- The three-dimensional sodium ion diffusion path is formed by the combination. The preparation process of this material inevitably generates sodium iron phosphate (NaFePO4) impurities, resulting in low actual capacity and great difficulty in industrialization. At present, the main iron source for preparing NFPP is ferric nitrate, but the cost of ferric nitrate is high, the decomposition products are harmful to the environment, and it is easy to explode. The mixture with combustibles is easy to ignite and burn violently, which poses a high safety hazard. Therefore, choosing a low-cost, more environmentally friendly and safer iron source to prepare NFPP has become an important issue for the practical application of NFPP. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing composite sodium ferric pyrophosphate by sulfur cycle, which has the characteristics of low cost, high reversible specific capacity and green environmental protection.

[0005] The present invention can be implemented by the following technical solutions: The invention discloses a method for preparing composite sodium ferric pyrophosphate by sulfur cycle, comprising the following steps: S1. Preparation of composite sodium ferric pyrophosphate: wet-mix ferrous sulfate, a sodium source, a phosphorus source, and a dispersant, spray-dry the mixture to obtain a precursor, and calcine the mixture at a high temperature under a protective atmosphere to obtain composite sodium ferric pyrophosphate; S2, tail gas recovery and conversion: The sulfur-containing tail gas and air generated during the high-temperature calcination of the precursor are simultaneously passed through a multi-layer vanadium pentoxide catalyst, and the temperature-controlled reaction realizes the conversion of SO2 into SO3 to obtain SO3 tail gas; S3, SO3 tail gas collection and conversion: SO3 tail gas is transferred into the sulfuric acid collector through the heat exchanger to realize the cooling and conversion of SO3 and H2O into sulfuric acid solution; S4, preparation of ferrous sulfate: adding an iron source to a sulfuric acid solution, heating for reaction, solid-liquid separation, cooling, adding a reducing agent for reaction, and obtaining a ferrous sulfate solution for step S1.

[0006] Undissolved solid matter is removed by solid-liquid separation to obtain a recovered solution. Since the iron source may contain high-valent iron, and oxygen in the air will oxidize ferrous ions in the recovered solution, a reducing agent is added to the recovered solution after cooling to room temperature, and solid-liquid separation is performed to remove solid product impurities after the redox reaction to obtain a ferrous sulfate solution. Specifically, the solid-liquid separation method includes one or more of filtration, suction filtration, filter press, and centrifugation.

[0007] In the present invention, ferrous sulfate with high safety and low cost is prepared through sulfur cycle to replace ferric nitrate as the iron source. Na4Fe3(PO4)2P2O7 precursor is synthesized by spray drying method, and composite sodium iron phosphate (NFPP) is obtained by high temperature calcination under protective atmosphere. 2+ Fe 3+ It does not need to be reduced by carbon produced by high-temperature decomposition, which reduces the process of carbon thermal reduction and produces Na4Fe3(PO4)2P2O7 with smaller grains and more stable lattice, so that the Na4Fe3(PO4)2P2O7 material synthesized from ferrous sulfate exhibits better performance than ferric nitrate.

[0008] Furthermore, in step S1, the molar ratio of the sodium element in the sodium source, the iron element in the ferrous sulfate, and the phosphorus element in the phosphorus source is 4: (2.91-3): 4; when the molar amount of the iron element in the iron source is too low, sodium iron pyrophosphate (NaFe2P2O7) with a low average working voltage and a low theoretical capacity will be derived, and the sodium iron pyrophosphate occupies a certain weight in the Na4Fe3(PO4)2P2O7 material, which will affect the release of the Na4Fe3(PO4)2P2O7 capacity; and when the molar amount of the iron element in the iron source is too high, a large amount of sodium iron phosphate (NaFePO4) impurities with no electrochemical activity will be derived, and the sodium iron phosphate occupies a certain weight in the Na4Fe3(PO4)2P2O7 material, so that the synthesized Na4Fe3(PO4)2P2O7 material exhibits a lower actual capacity.

[0009] Furthermore, in step S2, the flow rate ratio of sulfur-containing tail gas to air is 1:5-10, so as to ensure that sulfur dioxide is fully contacted and mixed with oxygen in the air to react under the action of the catalyst, while avoiding excessive air flow rate resulting in a low proportion of sulfur-containing gas and low yield; the vanadium pentoxide catalyst is a plate-like structure with 3-5 plate layers. If the number of plate-like catalyst layers is less than 3, sulfur dioxide and air cannot fully contact with the catalyst for reaction; if the number of plate-like catalyst layers is more than 5, the cost will become higher; the temperature of the temperature-controlled reaction is 400-600°C, and the reaction rate is low below 400°C; the activity of the catalyst is low above 600°C.

[0010] Furthermore, in step S3, the temperature range of the SO3 tail through the heat exchanger is 100-150°C. The cost of heat dissipation below 100°C is high, and the gas temperature is too high above 150°C, which will cause a large amount of water to evaporate, affecting the yield of sulfuric acid; the molar ratio of SO3 to water in the sulfuric acid collector is 1:2-5. When the molar amount of water is too low, sulfur trioxide cannot fully contact with water to react to generate sulfuric acid; when the molar amount of water is too high, the sulfuric acid content in the solution is low, which will increase the cost of subsequent evaporation of the solution.

[0011] Furthermore, in step S4, the molar ratio of sulfuric acid to iron in the iron source is 1:1-3, and the reaction time is 4-12h, so as to ensure that the sulfuric acid can react completely while saving the cost and time cost of the iron source; the heating temperature is 60-70°C, and the reaction rate of sulfuric acid and the iron source is slow and insufficient below 60°C, and the cost of heating above 70°C is high.

[0012] Furthermore, in step S4, the molar ratio of ferrous sulfate to the added reducing agent is 1:0.01-1. When the molar ratio of the added reducing agent is too low, the trivalent iron and the reducing agent cannot react completely. When the molar ratio of the added reducing agent is too high, the cost of the reducing agent becomes high, which is not economical. The reducing agent is one or more of iron wire, iron powder, iron block, hydrogen sulfide gas, and hydrogen sulfide solution.

[0013] Further, in step S4, the ferrous sulfate solution is evaporated and concentrated under a protective atmosphere, and cooled to precipitate ferrous sulfate crystals, and the ferrous sulfate crystals are directly added to step S1 for preparing composite sodium ferric pyrophosphate; the protective atmosphere is one or more of nitrogen, argon, and helium; the solution is evaporated and concentrated to 0.5-0.8 of the total volume, while saving costs and ensuring that as many ferrous sulfate crystals as possible are precipitated; the cooling temperature is 10-30°C, when the cooling temperature is below 10°C, a large amount of ice water is required, the cost becomes high, and when the cooling temperature is above 30°C, the ferrous sulfate crystals cannot be fully precipitated.

[0014] Furthermore, in step S1, the high temperature calcination temperature is 500-600°C and the holding time is 5-15h to ensure sufficient crystal growth of the material while saving the heating cost; the protective atmosphere is one or more of nitrogen, argon and helium.

[0015] Furthermore, in step S1, a carbon source is also added at the same time, and the amount of the carbon source added is 2%-10% of the total solid content; the carbon source is one or more of citric acid, starch, maltose, sucrose, glucose, L-ascorbic acid (vitamin C, abbreviated as VC), carbon nanotubes, graphene, and graphite.

[0016] Furthermore, the added form of ferrous sulfate is one or more of ferrous sulfate heptahydrate, ferrous sulfate pentahydrate, ferrous sulfate monohydrate, and anhydrous ferrous sulfate.

[0017] Furthermore, the sodium source is one or more of sodium carbonate, sodium acetate, sodium dihydrogen phosphate, sodium monohydrogen phosphate, sodium phosphate, sodium nitrate, sodium sulfate, sodium oxalate, sodium citrate, sodium pyrophosphate, and disodium dihydrogen pyrophosphate.

[0018] Furthermore, the phosphorus source is one or more of sodium phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, sodium pyrophosphate, and disodium dihydrogen pyrophosphate.

[0019] Furthermore, the dispersant is one or more of polyethylene glycol series, polyvinyl alcohol series, polyvinyl pyrrolidone series, polyacrylic acid series, and carboxymethyl cellulose series.

[0020] The present invention discloses a method for preparing composite sodium ferric pyrophosphate by sulfur cycle, which has the following beneficial effects: First, the reversible specific capacity is high. Ferrous sulfate is used as the iron source, and it is evenly mixed with a sodium source, a phosphorus source, a carbon source, a dispersant, and water. The Na4Fe3(PO4)2P2O7 (NFPP) powder material is obtained by spray drying and calcining. Due to the Fe 2+ Fe 3+ The carbon reduction produced by the high-temperature decomposition of the carbon source is not required, and the carbon thermal reduction process is reduced, so the NFPP carbon-coated composite positive electrode material with smaller grains and more stable lattices is generated, and the capacity can be fully utilized, greatly improving the actual discharge specific capacity. At the same time, the ferrous sulfate heptahydrate prepared by the sulfur cycle method is wet-mixed with the sodium source, phosphorus source, carbon source, and dispersant, and then spray-dried to obtain a precursor, which is calcined under a protective atmosphere to successfully obtain NFPP. Moreover, the synthesized NFPP has better constant current charge / discharge performance than the NFPP synthesized by ferric nitrate, which is beneficial to industrial production.

[0021] Second, the cost is low. Ferrous sulfate is used instead of ferric nitrate as the iron source to synthesize Na4Fe3(PO4)2P2O7 (NFPP) with excellent constant current charge / discharge performance, which reduces the cost. In addition, the present invention recycles the toxic gases SO2 and SO3 generated by high-temperature calcination of ferrous sulfate in the process of preparing NFPP to generate sulfuric acid, an important industrial raw material, and reacts sulfuric acid with an iron source to synthesize ferrous sulfate again. The synthesized ferrous sulfate can be used as a raw material, wet-mixed with a sodium source, a phosphorus source, a carbon source, and a dispersant, and then spray-dried to obtain a precursor, which is calcined under a protective atmosphere to prepare NFPP with better charge / discharge performance than ferric nitrate, realizing material circulation, greatly saving costs, and facilitating the commercial production of NFPP.

[0022] Third, it is green and environmentally friendly. Ferric nitrate is easy to make explosions, and its decomposition products are harmful to the environment. Its mixture with combustibles is easy to ignite and will burn violently, posing a high safety hazard. Compared with ferric nitrate, ferrous sulfate is not only cheap and low in cost, but also safer and more environmentally friendly. It does not belong to explosive hazardous chemicals and is more conducive to industrial production. In addition, the present invention utilizes a sulfur cycle method to recycle the toxic gases SO2 and SO3 produced by high-temperature calcination of ferrous sulfate in the process of preparing NFPP to generate sulfuric acid. The ferrous sulfate synthesized again by the reaction of sulfuric acid and iron source can be used as a raw material, wet mixed with sodium source, phosphorus source, carbon source, and dispersant, and then spray dried, and calcined under a protective atmosphere to prepare NFPP, thereby realizing the sulfur element cycle, being more environmentally friendly and environmentally friendly. DETAILED DESCRIPTION

[0023] In order to enable those skilled in the art to better understand the technical solution of the present invention, the product of the present invention is further described in detail below in conjunction with embodiments.

[0024] The invention discloses a method for preparing composite sodium ferric pyrophosphate by sulfur cycle, comprising the following steps: S1. Preparation of composite sodium ferric pyrophosphate: wet-mix ferrous sulfate, a sodium source, a phosphorus source, and a dispersant, spray-dry the mixture to obtain a precursor, and calcine the mixture at a high temperature under a protective atmosphere to obtain composite sodium ferric pyrophosphate; S2, tail gas recovery and conversion: The sulfur-containing tail gas and air generated during the high-temperature calcination of the precursor are simultaneously passed through a multi-layer vanadium pentoxide catalyst, and the temperature-controlled reaction realizes the conversion of SO2 into SO3 to obtain SO3 tail gas; S3, SO3 tail gas collection and conversion: SO3 tail gas is transferred into the sulfuric acid collector through the heat exchanger to realize the cooling and conversion of SO3 and H2O into sulfuric acid solution; S4, preparation of ferrous sulfate: adding an iron source to a sulfuric acid solution, heating for reaction, solid-liquid separation, cooling, adding a reducing agent for reaction, and obtaining a ferrous sulfate solution for step S1.

[0025] Furthermore, in step S1, the molar ratio of the sodium element in the sodium source, the iron element in the ferrous sulfate, and the phosphorus element in the phosphorus source is 4:(2.91-3):4.

[0026] Furthermore, in step S2, the flow rate ratio of sulfur-containing tail gas to air is 1:5-10; the vanadium pentoxide catalyst is a plate-like structure, and the number of plate layers is 3-5; the temperature of the temperature-controlled reaction is 400-600°C.

[0027] Further, in step S3, the temperature range of the SO3 tail through the heat exchanger is 100-150°C, and the molar ratio of SO3 to water in the sulfuric acid collector is 1:2-5.

[0028] Further, in step S4, the molar ratio of sulfuric acid to iron in the iron source is 1:1-3, the reaction time is 4-12 hours, and the heating temperature is 60-70°C.

[0029] Furthermore, in step S4, the molar ratio of ferrous sulfate to the added reducing agent is 1:0.01-1; the reducing agent is one or more of iron wire, iron powder, iron block, hydrogen sulfide gas, and hydrogen sulfide solution.

[0030] Further, in step S4, the ferrous sulfate solution is evaporated and concentrated under a protective atmosphere, and cooled to precipitate ferrous sulfate crystals, and the ferrous sulfate crystals are directly added to step S1 for preparing composite sodium ferric pyrophosphate; the protective atmosphere is one or more of nitrogen, argon, and helium; the solution is evaporated and concentrated to 0.5-0.8 of the total volume; and the cooling temperature is 10-30°C.

[0031] Furthermore, in step S1, the high temperature calcination temperature is 500-600°C, and the holding time is 5-15h; the protective atmosphere is one or more of nitrogen, argon, and helium.

[0032] Furthermore, in step S1, a carbon source is also added at the same time, and the amount of the carbon source added is 2%-10% of the total solid content; the carbon source is one or more of citric acid, starch, maltose, sucrose, glucose, L-ascorbic acid (vitamin C, abbreviated as VC), carbon nanotubes, graphene, and graphite.

[0033] Furthermore, the added form of ferrous sulfate is one or more of ferrous sulfate heptahydrate, ferrous sulfate pentahydrate, ferrous sulfate monohydrate, and anhydrous ferrous sulfate.

[0034] Furthermore, the sodium source is one or more of sodium carbonate, sodium acetate, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium phosphate, sodium nitrate, sodium sulfate, sodium oxalate, and sodium citrate.

[0035] Furthermore, the phosphorus source is one or more of sodium phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, sodium pyrophosphate, and disodium dihydrogen pyrophosphate.

[0036] Furthermore, the dispersant is one or more of polyethylene glycol series, polyvinyl alcohol series, polyvinyl pyrrolidone series, polyacrylic acid series, and carboxymethyl cellulose series.

[0037] Example 1 This embodiment relates to a method for preparing composite sodium ferric pyrophosphate by sulfur cycle, which specifically comprises the following steps: (1) FeSO4·7H2O and sodium dihydrogen phosphate dihydrate were mixed uniformly with citric acid (added in an amount of 2% of the total solid content), polyethylene glycol (added in an amount of 2% of the total solid content) and pure water in a molar ratio of 2.91:4 by magnetic stirring. The above solution was spray dried with an inlet air temperature of 240°C and an outlet air temperature of 100°C to achieve solid-liquid separation and obtain a dry precursor powder. Then, it was calcined at 600°C for 5h under a nitrogen atmosphere and NFPP was obtained after natural cooling. NFPP, acetylene black and 4% PVDF were mixed and homogenized in a mass ratio of 8:1:1. Then, the black slurry was coated on aluminum foil using a 120um four-sided preparation device and dried in an oven at 100°C for 2h. The electrode film was punched into a disc with a radius of 6 mm using a punching machine. Metallic sodium was used as the counter electrode, 1 mol / L NaClO4EC+DEC (1:1 vol%) + 5% FEC was used as the electrolyte, and the separator was a PP / PE / PP three-layer separator. A CR2032 button battery was assembled in a glove box for testing.

[0038] (2) The sulfur-containing tail gas and air generated during the high-temperature calcination of the precursor are introduced into the three-layer plate-like structure of vanadium pentoxide at a flow rate ratio of 1:5, and react at 400°C, and SO2 and oxygen in the air are converted into SO3.

[0039] (3) The mixed gas passes through a heat exchanger to 100°C and enters a sulfuric acid collector. The molar ratio of sulfur trioxide to water in the sulfuric acid collector is 1:2, and sulfuric acid is directly generated by the reaction.

[0040] (4) Add iron powder to sulfuric acid solution (molar ratio of sulfuric acid to iron powder is 1:1), heat to 60 °C for 12 h, and then filter to recover the solution. Pass hydrogen sulfide gas (molar ratio of ferrous sulfate to hydrogen sulfide is 1:0.01) into the recovered solution cooled to room temperature, and filter to remove the solid product impurities after the redox reaction to obtain ferrous sulfate solution. Under argon atmosphere, evaporate and concentrate the ferrous sulfate solution to 0.5 of the total volume, cool to 10 °C, and precipitate FeSO4·7H2O crystals.

[0041] (5) Repeat step (1) with the FeSO4·7H2O crystals obtained in step (4) to synthesize NFPP, and assemble them into CR2032 button batteries for testing.

[0042] Example 2 This embodiment relates to a method for preparing composite sodium ferric pyrophosphate by sulfur cycle, which specifically comprises the following steps: (1) FeSO4·5H2O, sodium acetate, and ammonium dihydrogen phosphate were uniformly mixed with citric acid (added in an amount of 10% of the total solid content), polyvinyl pyrrolidone (added in an amount of 10% of the total solid content), and pure water in a molar ratio of 3:4:4 by ultrasound. The above solution was spray-dried with an inlet air temperature of 230°C and an outlet air temperature of 95°C to achieve solid-liquid separation and obtain a dry precursor powder. Then, it was calcined at 500°C for 15h under an argon atmosphere and NFPP was obtained after natural cooling. NFPP, acetylene black, and 4% PVDF were mixed and homogenized in a mass ratio of 8:1:1. Then, the black slurry was coated on aluminum foil using a 120um four-sided preparation device and dried in an oven at 100°C for 2h. The electrode film was punched into a disc with a radius of 6 mm using a punching machine. Metallic sodium was used as the counter electrode, 1 mol / L NaClO4EC+DEC (1:1 vol%) + 5% FEC was used as the electrolyte, and the separator was a PP / PE / PP three-layer separator. A CR2032 button battery was assembled in a glove box for testing.

[0043] (2) The sulfur-containing tail gas and air generated during the high-temperature calcination of the precursor are introduced into the vanadium pentoxide with a five-layer plate structure at a flow rate ratio of 1:10, and react at 600°C, and SO2 and oxygen in the air are converted into SO3.

[0044] (3) The gas passes through a heat exchanger to 150°C and enters a sulfuric acid collector. The molar ratio of sulfur trioxide to water in the sulfuric acid collector is 1:5, and sulfuric acid is directly generated by the reaction.

[0045] (4) Add ferrous oxide to sulfuric acid solution (the molar ratio of sulfuric acid to ferrous oxide is 1:3), heat to 70 °C for 4 hours, and then recover the solution by filter pressing. Add iron powder (the molar ratio of ferrous sulfate to iron powder is 1:1) to the recovered solution cooled to room temperature, and remove the solid product impurities after the redox reaction by filter pressing to obtain ferrous sulfate solution. In a helium atmosphere, evaporate and concentrate the ferrous sulfate solution to 0.8 of the total volume, cool to 30 °C, and precipitate FeSO4·7H2O crystals.

[0046] (5) Repeat step (1) with the FeSO4·7H2O crystals obtained in step (4) to synthesize NFPP, and assemble them into CR2032 button batteries for testing.

[0047] Example 3 This embodiment relates to a method for preparing composite sodium ferric pyrophosphate by sulfur cycle, which specifically comprises the following steps: (1) FeSO4·H2O, sodium carbonate, and ammonium dihydrogen phosphate were uniformly mixed with glucose (added in an amount of 4% of the total solid content), L-ascorbic acid (vitamin C, added in an amount of 2% of the total solid content), polyvinyl alcohol (added in an amount of 6% of the total solid content), and pure water by ultrasound in a molar ratio of 2.95:4:4. The above solution was spray-dried with an inlet air temperature of 250°C and an outlet air temperature of 105°C to achieve solid-liquid separation and obtain a dry precursor powder. Then, it was calcined at 550°C for 10 hours in a helium atmosphere and NFPP was obtained after natural cooling. NFPP, acetylene black, and 4% PVDF were mixed and homogenized in a mass ratio of 8:1:1. Then, the black slurry was coated on aluminum foil using a 120um four-sided preparation device and dried in an oven at 100°C for 2 hours. The electrode film was punched into a disc with a radius of 6 mm using a punching machine. Metallic sodium was used as the counter electrode, 1 mol / L NaClO4EC+DEC (1:1 vol%) + 5%FEC was used as the electrolyte, and the separator was a PP / PE / PP three-layer separator. A CR2032 button cell was assembled in a glove box for testing.

[0048] (2) The sulfur-containing tail gas and air generated during the high-temperature calcination of the precursor are introduced into the vanadium pentoxide with a four-layer plate structure at a flow rate ratio of 1:7, and react at 500°C, and SO2 and oxygen in the air are converted into SO3.

[0049] (3) The gas passes through a heat exchanger to 120°C and enters a sulfuric acid collector. The molar ratio of sulfur trioxide to water in the sulfuric acid collector is 1:4, and sulfuric acid is directly generated by the reaction.

[0050] (4) Add iron filings to sulfuric acid solution (the molar ratio of sulfuric acid to iron filings is 1:2), heat to 65°C for 8 hours, and then recover the solution by centrifugation. Add hydrogen sulfide solution (the molar ratio of ferrous sulfate to hydrogen sulfide in the hydrogen sulfide solution is 1:0.5) to the recovered solution cooled to room temperature, remove the solid product impurities after the redox reaction by centrifugation, and obtain ferrous sulfate solution. Under a nitrogen atmosphere, evaporate and concentrate the ferrous sulfate solution to 0.6 of the total volume, cool to 25°C, and precipitate FeSO4·7H2O crystals.

[0051] (5) Repeat step (1) with the FeSO4·7H2O crystals obtained in step (4) to synthesize NFPP, and assemble them into CR2032 button batteries for testing.

[0052] Example 4 This embodiment relates to a method for preparing composite sodium ferric pyrophosphate by sulfur cycle, which specifically comprises the following steps: (1) Anhydrous ferrous sulfate and sodium dihydrogen phosphate dihydrate were mixed in a molar ratio of 3:4 with citric acid (added in an amount of 2% of the total solid content), polyethylene glycol (added in an amount of 2% of the total solid content), and pure water by magnetic stirring. The above solution was spray dried with an inlet air temperature of 240°C and an outlet air temperature of 100°C to achieve solid-liquid separation and obtain a dry precursor powder. Then, it was calcined at 500°C for 10 hours under a nitrogen atmosphere and NFPP was obtained after natural cooling. NFPP, acetylene black, and 4% PVDF were mixed and slurried in a mass ratio of 8:1:1. Then, the black slurry was coated on aluminum foil using a 120um four-sided preparation device and dried in an oven at 100°C for 2 hours. The electrode film was punched into a disc with a radius of 6 mm using a punching machine. Metallic sodium was used as the counter electrode, 1 mol / L NaClO4EC+DEC (1:1 vol%) + 5% FEC was used as the electrolyte, and the separator was a PP / PE / PP three-layer separator. A CR2032 button battery was assembled in a glove box for testing.

[0053] (2) The sulfur-containing tail gas and air generated during the high-temperature calcination of the precursor are introduced into the vanadium pentoxide with a five-layer plate structure at a flow rate ratio of 1:5, and react at 600°C, and SO2 and oxygen in the air are converted into SO3.

[0054] (3) The mixed gas passes through a heat exchanger to 130°C and enters a sulfuric acid collector. The molar ratio of sulfur trioxide to water in the sulfuric acid collector is 1:2, and sulfuric acid is directly generated by the reaction.

[0055] (4) Add iron powder to sulfuric acid solution (molar ratio of sulfuric acid to iron powder is 1:1), heat to 70°C for 12 hours, and then filter to recover the solution. Pass hydrogen sulfide gas (molar ratio of ferrous sulfate to hydrogen sulfide is 1:0.01) into the recovered solution cooled to room temperature, and filter to remove the solid product impurities after the redox reaction to obtain ferrous sulfate solution. Under argon atmosphere, evaporate and concentrate the ferrous sulfate solution to 0.5 of the total volume, cool to 30°C, and precipitate FeSO4·7H2O crystals.

[0056] (5) Repeat step (1) with the FeSO4·7H2O crystals obtained in step (4) to synthesize NFPP, and assemble them into CR2032 button batteries for testing.

[0057] Example 5 This embodiment relates to a method for preparing composite sodium ferric pyrophosphate by sulfur cycle, which specifically comprises the following steps: (1) FeSO4·7H2O, sodium acetate and diammonium hydrogen phosphate were uniformly mixed with citric acid (added amount was 10% of the total solid content), polyvinyl pyrrolidone (added amount was 10% of the total solid content) and pure water in a molar ratio of 2.91:4:4 by ultrasound. The above solution was spray dried with an inlet air temperature of 230°C and an outlet air temperature of 95°C to achieve solid-liquid separation and obtain a dry precursor powder. Then, it was calcined at 550°C for 15h under an argon atmosphere and NFPP was obtained after natural cooling. NFPP, acetylene black and 4% PVDF were mixed and homogenized in a mass ratio of 8:1:1. Then, the black slurry was coated on aluminum foil using a 120um four-sided preparation device and dried in an oven at 100°C for 2h. The electrode film was punched into a disc with a radius of 6 mm using a punching machine. Metallic sodium was used as the counter electrode, 1 mol / L NaClO4EC+DEC (1:1 vol%) + 5%FEC was used as the electrolyte, and the separator was a PP / PE / PP three-layer separator. A CR2032 button cell was assembled in a glove box for testing.

[0058] (2) The sulfur-containing tail gas and air generated during the high-temperature calcination of the precursor are introduced into the three-layer plate-like structure of vanadium pentoxide at a flow rate ratio of 1:8, and react at 450°C, and SO2 and oxygen in the air are converted into SO3.

[0059] (3) The gas passes through a heat exchanger to 100°C and enters a sulfuric acid collector. The molar ratio of sulfur trioxide to water in the sulfuric acid collector is 1:5, and sulfuric acid is directly generated by the reaction.

[0060] (4) Add ferrous oxide to sulfuric acid solution (the molar ratio of sulfuric acid to ferrous oxide is 1:3), heat to 65°C for reaction for 8 hours, and then recover the solution by filter pressing. Add iron powder (the molar ratio of ferrous sulfate to iron powder is 1:0.5) to the recovered solution cooled to room temperature, and remove the solid product impurities after the redox reaction by filter pressing to obtain ferrous sulfate solution. In a helium atmosphere, evaporate and concentrate the ferrous sulfate solution to 0.8 of the total volume, cool to 20°C, and precipitate FeSO4·7H2O crystals.

[0061] (5) Repeat step (1) with the FeSO4·7H2O crystals obtained in step (4) to synthesize NFPP, and assemble them into CR2032 button batteries for testing.

[0062] Example 6 This embodiment relates to a method for preparing composite sodium ferric pyrophosphate by sulfur cycle, which specifically comprises the following steps: (1) FeSO4·5H2O, sodium nitrate and ammonium dihydrogen phosphate were mixed uniformly with glucose (added in an amount of 5% of the total solid content), L-ascorbic acid (vitamin C, added in an amount of 3% of the total solid content), polyethylene glycol (added in an amount of 8% of the total solid content) and pure water by ultrasound in a molar ratio of 2.97:4:4. The above solution was spray dried with an inlet air temperature of 250°C and an outlet air temperature of 105°C to achieve solid-liquid separation and obtain a dry precursor powder. Then, it was calcined at 600°C for 10 hours in a helium atmosphere and NFPP was obtained after natural cooling. NFPP, acetylene black and 4% PVDF were mixed and homogenized in a mass ratio of 8:1:1. Then, the black slurry was coated on aluminum foil using a 120um four-sided preparation device and dried in an oven at 100°C for 2 hours. The electrode film was punched into a disc with a radius of 6 mm using a punching machine. Metallic sodium was used as the counter electrode, 1 mol / L NaClO4EC+DEC (1:1 vol%) + 5%FEC was used as the electrolyte, and the separator was a PP / PE / PP three-layer separator. A CR2032 button cell was assembled in a glove box for testing.

[0063] (2) The sulfur-containing tail gas and air generated during the high-temperature calcination of the precursor are introduced into the vanadium pentoxide with a four-layer plate structure at a flow rate ratio of 1:7, and react at 550°C, and SO2 and oxygen in the air are converted into SO3.

[0064] (3) The gas passes through a heat exchanger to 130°C and enters a sulfuric acid collector. The molar ratio of sulfur trioxide to water in the sulfuric acid collector is 1:4, and sulfuric acid is directly generated by the reaction.

[0065] (4) Add iron filings to sulfuric acid solution (the molar ratio of sulfuric acid to iron filings is 1:1.5), heat to 60°C for reaction for 8 hours, and then recover the solution by centrifugation. Add hydrogen sulfide solution (the molar ratio of ferrous sulfate to hydrogen sulfide in the hydrogen sulfide solution is 1:0.1) to the recovered solution cooled to room temperature, remove the solid product impurities after the redox reaction by centrifugation, and obtain ferrous sulfate solution. Under a nitrogen atmosphere, evaporate and concentrate the ferrous sulfate solution to 0.6 of the total volume, cool to 10°C, and precipitate FeSO4·7H2O crystals.

[0066] (5) Repeat step (1) with the FeSO4·7H2O crystals obtained in step (4) to synthesize NFPP, and assemble them into CR2032 button batteries for testing.

[0067] Comparative Example 1 This embodiment relates to composite sodium iron pyrophosphate, and its preparation method comprises the following steps: Fe(NO3)3·9H2O was used as an iron source and sodium dihydrogen phosphate dihydrate was mixed with citric acid (added in an amount of 2% of the total solid content), polyethylene glycol (added in an amount of 2% of the total solid content) and pure water in a molar ratio of 3:4 by magnetic stirring. The above solution was spray dried with an inlet air temperature of 230°C and an outlet air temperature of 95°C to achieve solid-liquid separation and obtain a dry precursor powder. After that, it was calcined at 500°C for 15h under an argon atmosphere and NFPP was obtained after natural cooling. NFPP, acetylene black and 4% PVDF were mixed and homogenized in a mass ratio of 8:1:1. Then, the black slurry was coated on aluminum foil using a 120um four-sided preparation device and dried in an oven at 100°C for 2h. The electrode film was punched into a disc with a radius of 6 mm using a punching machine. Metallic sodium was used as the counter electrode, 1 mol / L NaClO4EC+DEC (1:1 vol%) + 5%FEC was used as the electrolyte, and the separator was a PP / PE / PP three-layer separator. A CR2032 button cell was assembled in a glove box for testing.

[0068] Comparative Example 2 This embodiment relates to composite sodium iron pyrophosphate, and its preparation method comprises the following steps: Fe(NO3)3·9H2O was mixed with sodium acetate and ammonium dihydrogen phosphate in a molar ratio of 2.91:4:4, glucose (added in an amount of 10% of the total solid content), polyvinyl alcohol (added in an amount of 10% of the total solid content), and pure water by ultrasound. The above solution was spray dried with an inlet air temperature of 240°C and an outlet air temperature of 100°C to achieve solid-liquid separation and obtain a dry precursor powder. After that, it was calcined at 600°C for 5h under a nitrogen atmosphere and NFPP was obtained after natural cooling. NFPP, acetylene black, and 4% PVDF were mixed and homogenized in a mass ratio of 8:1:1. Then, the black slurry was coated on aluminum foil using a 120um four-sided preparation device and dried in an oven at 100°C for 2h. The electrode film was punched into a disc with a radius of 6 mm using a punching machine. Metallic sodium was used as the counter electrode, 1 mol / L NaClO4EC+DEC (1:1 vol%) + 5%FEC was used as the electrolyte, and the separator was a PP / PE / PP three-layer separator. A CR2032 button cell was assembled in a glove box for testing.

[0069] The constant current charge and discharge data of Na4Fe3(PO4)2P2O7 (NFPP) prepared in Examples 1-6 and Comparative Examples 1 and 2 are as follows: Table 1 Performance test results As can be seen from Table 1, the constant current charge-discharge specific capacity of NFPP synthesized by ferrous sulfate in step 1 of Examples 1-6 is better than that of NFPP synthesized by Fe(NO3)3·9H2O in Comparative Examples 1 and 2, which shows that it is completely feasible to use ferrous sulfate with low cost and higher safety to synthesize Na4Fe3(PO4)2P2O7 (NFPP), and the synthesized NFPP has better charge-discharge performance. At the same time, the constant current charge-discharge specific capacity of NFPP synthesized by sulfur cycle in step 5 of Examples 1, 2, 3, 4, 5, and 6 is also better than that of NFPP prepared by Fe(NO3)3·9H2O in Comparative Examples 1 and 2, which shows that the method of preparing composite sodium iron pyrophosphate by sulfur cycle of the present invention is completely feasible.

[0070] The above embodiments are only specific embodiments of the present invention, and their descriptions are relatively specific and detailed, but they cannot be understood as limiting the scope of the present invention. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, and these obvious replacement forms all belong to the protection scope of the present invention.

Claims

1. A method for preparing composite sodium ferric pyrophosphate by sulfur cycle, characterized in that The following steps are involved: S1. Preparation of composite sodium ferric pyrophosphate: wet-mix ferrous sulfate, a sodium source, a phosphorus source, and a dispersant, spray-dry the mixture to obtain a precursor, and calcine the mixture at a high temperature under a protective atmosphere to obtain composite sodium ferric pyrophosphate; S2, tail gas recovery and conversion: The sulfur-containing tail gas and air generated during the high-temperature calcination of the precursor are simultaneously passed through a multi-layer vanadium pentoxide catalyst, and the temperature-controlled reaction realizes the conversion of SO2 into SO3 to obtain SO3 tail gas; S3, SO3 tail gas collection and conversion: SO3 tail gas is transferred into the sulfuric acid collector through the heat exchanger to realize the cooling and conversion of SO3 and H2O into sulfuric acid solution; S4, preparation of ferrous sulfate: adding an iron source to a sulfuric acid solution, heating for reaction, solid-liquid separation, cooling, adding a reducing agent for reaction, and obtaining a ferrous sulfate solution for step S1.

2. The method for preparing composite sodium ferric pyrophosphate by sulfur cycle according to claim 1, characterized in that: In step S1, the molar ratio of the sodium element in the sodium source, the iron element in the ferrous sulfate, and the phosphorus element in the phosphorus source is 4:(2.91-3):

4.

3. The method for preparing composite sodium ferric pyrophosphate by sulfur cycle according to claim 1, characterized in that: In step S2, the flow rate ratio of sulfur-containing tail gas to air is 1:5-10; the vanadium pentoxide catalyst is a plate-like structure, and the number of plate layers is 3-5; the temperature of the temperature-controlled reaction is 400-600°C.

4. The method for preparing composite sodium ferric pyrophosphate by sulfur cycle according to claim 1, characterized in that: In step S3, the temperature range of the SO3 tail through the heat exchanger is 100-150°C; the molar ratio of SO3 to water in the sulfuric acid collector is 1:2-5.

5. The method for preparing composite sodium ferric pyrophosphate by sulfur cycle according to claim 1, characterized in that: In step S4, the molar ratio of sulfuric acid to the iron element in the iron source is 1:1-3, the reaction time is 4-12 hours, and the heating temperature is 60-70°C.

6. The method for preparing composite sodium ferric pyrophosphate by sulfur cycle according to claim 1, characterized in that: In step S4, the molar ratio of ferrous sulfate to the added reducing agent is 1:0.01-1; the reducing agent is one or more of iron wire, iron powder, iron block, hydrogen sulfide gas, and hydrogen sulfide solution.

7. The method for preparing composite sodium ferric pyrophosphate by sulfur cycle according to claim 1, characterized in that: In step S4, the ferrous sulfate solution is evaporated and concentrated under a protective atmosphere, and cooled to precipitate ferrous sulfate crystals, which are directly added to step S1 for preparing composite sodium ferric pyrophosphate; the protective atmosphere is one or more of nitrogen, argon, and helium; the solution is evaporated and concentrated to 0.5-0.8 of the total volume; and the cooling temperature is 10-30°C.

8. The method for preparing composite sodium ferric pyrophosphate by sulfur cycle according to claim 7, characterized in that: In step S1, the high temperature calcination temperature is 500-600°C, and the holding time is 5-15h; the protective atmosphere is one or more of nitrogen, argon, and helium.

9. The method for preparing composite sodium ferric pyrophosphate by sulfur cycle according to claim 1, characterized in that: In step S1, a carbon source is also added at the same time, and the amount of the carbon source added is 2%-10% of the total solid content; the carbon source is one or more of citric acid, starch, maltose, sucrose, glucose, L-ascorbic acid (vitamin C, abbreviated as VC), carbon nanotubes, graphene, and graphite.

10. The method for preparing composite sodium ferric pyrophosphate by sulfur cycle according to claim 1, characterized in that: In step S1, the ferrous sulfate is added in the form of one or more of ferrous sulfate heptahydrate, ferrous sulfate pentahydrate, ferrous sulfate monohydrate, and anhydrous ferrous sulfate; The sodium source is one or more of sodium carbonate, sodium acetate, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium phosphate, sodium nitrate, sodium sulfate, sodium oxalate, sodium citrate, sodium pyrophosphate, and disodium dihydrogen pyrophosphate; The phosphorus source is one or more of sodium phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, sodium pyrophosphate, and disodium dihydrogen pyrophosphate; The dispersant is one or more of polyethylene glycol series, polyvinyl alcohol series, polyvinyl pyrrolidone series, polyacrylic acid series, and carboxymethyl cellulose series.

Citation Information

Patent Citations

  • Non-pollution polymeric iron sulfate sulfur production technique by dioxide reverse absorption tower process

    CN101037246A

  • Method for preparing sulfuric acid and cement by using phosphogypsum

    CN102530886A

  • Sodium-ion battery positive electrode material as well as preparation method and application thereof

    CN117239120A

  • Carbon-coated multi-element doped pyrophosphate ferric sodium phosphate and preparation method thereof

    CN118387852A

  • Positive electrode material for sodium-ion battery, and preparation method therefor and application thereof

    WO2023071396A1